Institutional versus noninstitutional credit to agricultural households in India: Evidence on impact from a national farmers’ survey - Kumar, Anjani; Mishra, Ashok K.; Saroj, Sunil; Joshi, Pramod Kumar (International Food Policy Research Institute, 2017)
A goal of agricultural policy in India has been to reduce farmers’ dependence on informal credit. To that end, recent initiatives have been focused explicitly on rural areas and have had a positive impact on the flow of agricultural credit. But despite the significance of these initiatives in enhancing the flow of institutional credit to agriculture, the links between institutional credit and net farm income and consumption expenditures in India are not very well documented. Using a large national farm household–level dataset and instrumental variables two-stage least squares estimation methods, we investigate the impact of institutional farm credit on farm income and farm household consumption expenditures. Our findings show that in India, formal credit is indeed playing a critical role in increasing both the net farm income and per capita monthly household expenditures of Indian farm families. We also find that, in the presence of formal credit, social safety net programs such as the Mahatma Gandhi National Rural Employment Guarantee Act (MGNREGA) may have unintended consequences. In particular, MGNREGA reduces both net farm income and per capita monthly household consumption expenditures. In contrast, in the presence of formal credit, the Public Distribution System may increase both net farm income and per capita monthly household consumption expenditures.